High‐performance liquid chromatography enantioseparation of polyhalogenated 4, 4′‐bipyridines on polysaccharide‐based chiral stationary phases under multimodal elution. Issue 18 (30th July 2014) - Peluso, Paola; Mamane, Victor; Aubert, Emmanuel; Cossu, Sergio
<x xml:space="preserve">Abstract</x> An investigation on the high‐performance liquid chromatography enantioseparation of 12 polyhalogenated 4, 4′‐bipyridines on polysaccharide‐based chiral stationary phases is described. The overall study was directed toward the generation of efficient separations in order to obtain pure atropisomers that will serve as ligands for building homochiral metal organic frameworks. Four coated columns—namely, Lux Cellulose‐1, Lux Cellulose‐2, Lux Cellulose‐4, and Lux Amylose‐2—and two immobilized columns—namely, Chiralpak IC and IA—were used under normal, polar organic, and reversed‐phase elution modes. Moreover, Chiralcel OJ was considered under normal‐phase and polar organic conditions. The effect of the chiral selector and mobile phase composition on the enantioseparation, the enantiomer elution order and the beneficial effect of nonstandard solvents were studied. The effect of water in the mobile phase on the enantioselectivity and retention was investigated and retention profiles typical of hydrophilic interaction liquid chromatography were observed. Interesting phenomena of solvent‐induced enantiomer elution order reversal occurred under normal‐phase mode. All the considered 4, 4′‐bipyridines were enantioseparated at the multimilligram level.